2001
DOI: 10.1046/j.1442-200x.2001.01360.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of portal and systemic bacteremia in acute appendicitis

Abstract: The results presented in this paper suggests that portal bacteremia did not influence peripheral blood reactions. Furthermore, in the present study we have found a positive correlation between the smear and bacteremia of the superior mesenteric vein, but not with the bacteremia of systemic blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 7 publications
1
21
1
Order By: Relevance
“…These inflammatory agents may also alter the hepatic blood flow and normal physiological flow of the bile causing hyperbilirubinemia. [3][4][5][6][7][8] Few other studies have compared various inflammatory agents with total bilirubin as a predictive marker of perforation of appendix.…”
mentioning
confidence: 99%
“…These inflammatory agents may also alter the hepatic blood flow and normal physiological flow of the bile causing hyperbilirubinemia. [3][4][5][6][7][8] Few other studies have compared various inflammatory agents with total bilirubin as a predictive marker of perforation of appendix.…”
mentioning
confidence: 99%
“…The rate of blood culture positivity in acute appendicitis is actually low. A prospective study revealed that systemic bacteraemia was 0% at 30 min before surgery and 6% during surgery 6. Furthermore, blood cultures became positive in only 10% of cases of acute appendicitis with perforation, and an extremely low percentage in appendicitis without perforation 7.…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that in appendicitis, bacteria can traverse the intact appendiceal wall prior to perforation and the number of bacteria that do this, increase when there is more inflammation and tissue damage present [6]. There is a high rate of portal bacteraemia (45%) seen in patients with confirmed appendicitis but due to the liver being an effective barrier in preventing bacteria entering the systemic circulation, only 7% have systemic bacteraemia [7].…”
Section: Discussionmentioning
confidence: 99%